STRATEGI PENGURANGAN PENGANGGURAN DI KABUPATEN SUMEDANG - Akadun; Lestari; Lia Agustiani (Journal Of Regional Public Administration (JRPA), 2021)
This research was conducted in Sumedang Regency because the number of labor force in Sumedang Regency is quite large, it can be seen from the results of a local government survey listed on the sumedangkab.go.id website in 2019 showing that the total population in Sumedang Regency was recorded at 1,154,458 people. This is higher when compared to the total population in Sumedang Regency in 2018 of 1,148,198 people which experienced an increase in population growth of 0.5%, and with an open unemployment rate of 9.1% where open unemployment was 40,847 people. In this regard, the authors are interested in conducting research at the Sumedang Regency Manpower Office to what extent the strategy undertaken by the Manpower Office in reducing unemployment in Sumedang. The focus of this research are: 1) How is the condition of unemployment in Sumedang Regency? 2) What is the strategy of the Office carried out by the Office of Manpower in reducing unemployment in Sumedang Regency? 3) What are the supporting factors and inhibiting factors of the Department of Manpower's strategy in reducing unemployment in Sumedang Regency? 4) What are the the inner solution offered by the Sumedang Regency manpower service in view of the inhibiting factors? As for the objectives of this study are: 1) To find the condition of unemployment in Sumedang District 2) To find out and explain the strategies undertaken by the Manpower Office in reducing unemployment in Sumedang District, 3) To find out the factors that support and inhibit the Department of Manpower's strategy in reducing unemployment in Sumedang District, 4) To find out the solutions offered by the Sumedang Regency Manpower Office related to inhibiting factors. The research method used by researchers in this study is a qualitative research method with the type of case study research, while the approach used is a descriptive approach. Data collection techniques used in this study include observation, in-depth interviews and documentation. Data analysis techniques used by researchers in this study are data reduction, data presentation and drawing conclusions, checking the validity of the data in this study include trust, transferability, dependability, and confirmability.